2006
DOI: 10.1016/j.gca.2005.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Natural-abundance radiocarbon as a tracer of assimilation of petroleum carbon by bacteria in salt marsh sediments

Abstract: The natural abundance of radiocarbon ( 14 C ) provides unique insight into the source and cycling of sedimentary organic matter. Radiocarbon analysis of bacterial phospholipid lipid fatty acids (PLFAs) in salt-marsh sediments of southeast Georgia (USA) -one heavily contaminated by petroleum residues -was used to assess the fate of petroleum-derived carbon in sediments and incorporation of fossil carbon into microbial biomass. PLFAs that are common components of eubacterial cell membranes (e.g., branched C 15 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 68 publications
2
45
1
Order By: Relevance
“…Lipid extracts obtained by accelerated solvent extraction (ASE) using dichloromethane : methanol (9 : 1) were saponified, and the recovered FA were methylated with BF 3 -MeOH. Two fatty acid methyl ester (FAME) composites were obtained by preparative capillary gas chromatography (Eglinton et al, 1997;Wakeham et al, 2006): short-chain FAME (n-C 14 -n-C 18 ) and long-chain FAME (n-C 24 -n-C 28 ). Compositions, purity, and amounts of FAME isolates were checked by gas chromatography and analyzed subsequently for 13 C and 14 C. Corrections for the addition of carbon from the methyl group during methylation were made by mass balance.…”
Section: Carbon Isotope Analysismentioning
confidence: 99%
“…Lipid extracts obtained by accelerated solvent extraction (ASE) using dichloromethane : methanol (9 : 1) were saponified, and the recovered FA were methylated with BF 3 -MeOH. Two fatty acid methyl ester (FAME) composites were obtained by preparative capillary gas chromatography (Eglinton et al, 1997;Wakeham et al, 2006): short-chain FAME (n-C 14 -n-C 18 ) and long-chain FAME (n-C 24 -n-C 28 ). Compositions, purity, and amounts of FAME isolates were checked by gas chromatography and analyzed subsequently for 13 C and 14 C. Corrections for the addition of carbon from the methyl group during methylation were made by mass balance.…”
Section: Carbon Isotope Analysismentioning
confidence: 99%
“…Based on the fatty acid composition and d 13 C fatty acids, it has been found that bacteria within the sediments were dependent on the marine source of organic matter and mainly utilised a labile pool of organic matter that was derived from algae (Hu et al 2006). In turn, Wakeham et al (2006) calculated that 6-10 % of the carbon in bacterial PLFAs could have been derived from petroleum residues, which suggested that even weathered petroleum might contain components with sufficient viability to be a carbon source for microbial biomass production in marsh sediments. Examples of the fatty acid biomarkers detected in the sediment samples are presented in Table 2.…”
Section: Microbial Diversity In Sedimentsmentioning
confidence: 99%
“…It has been demonstrated that the use of the stable isotope probing (SIP) of RNA, DNA and PLFA biomarkers allows active members of microbial community to be identified and permits the phylogenetic lineages and functional activity of the microbial community structure to be established (Webster et al 2006). Isotope ratios of PLFAs allow the organic matter sources that are utilised by bacteria to be studied (Boschker and Middelburg 2002) and the incorporation of fossil carbon into the microbial biomass to be investigated (Wakeham et al 2006). PLFA analysis when used in conjunction with carbon isotope signature elucidates the carbon-cyclic pathways of bacteria and can indicate the potential carbon substrates for their metabolism (Boschker and Middelburg 2002;Holmer et al 2004;Zhang et al 2005;van den Meersche et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mollenhauer et al 2006). The influx of anthropogenic carbon, mostly from fossil fuel burning and spills have been extensively investigated (Reddy et al 2002a,b;Tanner et al 2004;Slater et al 2005Slater et al , 2006Smittenberg et al 2005;White et al 2005;Wakeham et al 2006). Interestingly, not all suspected pollution indicators are necessarily man-made.…”
Section: Biogeochemistry and Microscale Amsmentioning
confidence: 99%